Protective Effect of Quercetin Against Oxidative Stress-induced Toxicity Associated With Doxorubicin and Cyclophosphamide in Rat Kidney and Liver Tissue (Iranian Journal of Kidney Diseases, 2017)
Introduction. Doxorubicin and cyclophosphamide are widely used anticancer drugs with substantial toxicity in noncancerous tissue resulting from oxidative damage. Quercetin is a potent antioxidant compound. We hypothesized that quercetin administration would ameliorate the toxic effects of doxorubicin and cyclophosphamide prior to pregnancy. Materials and Methods. Cyclophosphamide, 27 mg/kg, and doxorubicin, 1.8 mg/kg, were administered to rats as intraperitoneal doses once every 3 weeks for a total of 10 weeks with or without concurrent treatment with quercetin, 10 mg/kg/d. Oxidative stress parameters were evaluated in maternal kidney and liver tissues after gestation. Results. Doxorubicin was associated with elevated kidney tissue malondialdehyde relative to the controls and quercetin only treatment (P < .05). Both cyclophosphamide and doxorubicin were associated with elevated malondialdehyde levels in the liver tissue (P < .05). Doxorubicin treatment was associated with decreased liver glutathione peroxidase (P < .05). Quercetin treatment suppressed the accumulation of malondialdehyde and increased glutathione peroxidase levels during doxorubicin and cyclophosphamide treatment (P